1999
DOI: 10.1007/s004240051102
|View full text |Cite
|
Sign up to set email alerts
|

Role of the D 2 dopamine receptor in molecular adaptation to chronic hypoxia in PC12 cells

Abstract: We have previously shown that pheochromocytoma (PC12) cells rapidly depolarize and undergo Ca 2+ influx through voltage-dependent Ca 2+ channels in response to moderate hypoxia and that intracellular free Ca 2+ is modulated by activation of dopamine D 2 receptors in this cell type. The present study shows that D 2 (quinpirole-mediated) inhibition of a voltage-dependent Ca 2+ current (I Ca ) in PC12 cells is dramatically attenuated after chronic exposure to moderate hypoxia (24 h at 10% O 2 ). Pretreatment of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These cells are catecholaminergic rat pheochromocytoma cells and can display a DA phenotype after differentiation with nerve growth factor (NGF) (Greene and Tischler, 1976;Tischler et al, 1983). They express D 2 , D 3 and D 4 receptors (Jorgensen and Richter-Landsberg, 1983;Damon et al, 1990;Pothos et al, 1998;Kobayashi et al, 1999;Chu et al, 2004) and DAT (Kadota et al, 1996). We report that DA agonists, Br and Qp, amplify specifically the effect of MPP + on cellular death and this event is prevented in the presence of DA antagonists.…”
Section: Fp Graham Publishing Comentioning
confidence: 93%
“…These cells are catecholaminergic rat pheochromocytoma cells and can display a DA phenotype after differentiation with nerve growth factor (NGF) (Greene and Tischler, 1976;Tischler et al, 1983). They express D 2 , D 3 and D 4 receptors (Jorgensen and Richter-Landsberg, 1983;Damon et al, 1990;Pothos et al, 1998;Kobayashi et al, 1999;Chu et al, 2004) and DAT (Kadota et al, 1996). We report that DA agonists, Br and Qp, amplify specifically the effect of MPP + on cellular death and this event is prevented in the presence of DA antagonists.…”
Section: Fp Graham Publishing Comentioning
confidence: 93%
“…channels, proton-gated channels, and ATP-evoked ionic pumps; neurotransmitter receptors such as cholinergic (muscarinic and nicotinic) receptors, dopamine receptors, adenosine and P2 receptors, serotonin-gated receptors, glutamate (metabotropic) receptors; neuromodulator receptors such as, opioid receptors, neuropeptide Y receptors and transporters such as catecholamine transporters, glucose transporters and divalent metal transporter etc. (Shafer and Atchison 1991;Clementi et al 1992;Margioris et al 1995;Park et al 1998;Kobayashi et al 1999;McCullough et al 1998;Arslan and Fredholm 1999;Kane et al 1998;Roth et al 2000;Ardizzone et al 2002;Chu et al 2002). Because of their unique properties and suitability for genetic manipulations, PC12 cells are regarded to be a convenient alternative to endogenous neuronal cells, and a model system for a range of studies such as, neuronal differentiation, neurotransmitter synthesis and exocytosis kinetics, mechanism of synaptotagmin, neurotrophin action, monoamine biosynthesis, ion channel and receptors modulations, protein trafficking, secretory vesicle dynamics, oxygen sensing, opioids and their receptor interaction mechanisms, cellular necrosis and apoptosis, cell signalling, neural plasticity, neuronal sprouting, gene expression, and neuronal diseases such as, Alzheimer's diseases, Huntington's disease, peripheral neuropathy and neurotoxicology (Greene and Rein 1977;Anderson et al 1991;Burgoyne 1991;Keilbaugh et al 1991;Isom et al 1998;Margioris et al 1995;Bal-Price and Brown 2000;Vaudry et al 2002a;Spicer and Millhorn 2003;Igarashi et al 2003;Martin and Grishanin 2003;Fukuda and Yamamoto 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Among these factors, most of attention has been attributed to the dopamine D2 receptor (DRD2) due to its pathological role in schizophrenia. DRD2 mRNA levels show an early and transient reduction in the striatum after hypoxia-ischemia in newborn rats [15], and attenuation of DRD2 mediated inhibition of calcium influx in pheochromocytoma cells has been reported in hypoxia [16]. On the other hand, Huey and Powell revealed that hypoxia modulates DRD2 expression in a tissue-dependent manner [17].…”
Section: Introductionmentioning
confidence: 99%